Beyond the Screen: Media Power, Religious Identity, and the Digital Defence of Pesantren in Contemporary Indonesia - Muhamad Zainal Mahendra (JSP: Jurnal Studi Pesantren, 2025)
The representation of Islamic boarding schools (pesantren) in Indonesian mainstream media has long been a site of tension between secular media logics and Islamic educational values, yet the specific dynamics of misrepresentation, public response, and regulatory intervention in the digital era remain underexplored. This study examines how the broadcast of Trans7's Xpose Uncensored programme in October 2025 triggered a crisis of pesantren representation, analyzes the digital counter-responses mounted by the santri community, and investigates the regulatory and political actions that followed. Employing a qualitative descriptive approach grounded in Critical Discourse Analysis (Fairclough, 1995) and thematic content analysis, this study draws on data from national online media, official institutional statements from KPID Banten, KPI, MUI, and DPR RI, and digital public responses across YouTube, Instagram, and X (Twitter). The findings reveal that the broadcast constructed a distorted image of pesantren life by decontextualizing ritual practices of respect (ta'dzim) as symbols of subjugation, thereby reproducing secular-capitalist discursive dominance over Islamic educational institutions. In response, the santri community mobilized a sustained digital counter-narrative through social media activism, transforming from passive media subjects into active producers of religious public discourse. Regulatory bodies subsequently confirmed broadcasting violations and imposed sanctions, while political and religious institutions affirmed the moral boundaries of permissible media representation. This study concludes that the pesantren community's digital response signals a significant shift in the socio-religious public sphere, and that ethical media governance in religiously plural societies requires institutional frameworks that are sensitive to the symbolic dimensions of faith-based education.